UPAYA PENINGKATAN PENDAPATAN ASLI DAERAH (PAD) KABUPATEN JEPARADALAM RANGKA MENYONGSONG OTONOMI DAERAH DAN PERIMBANGAN KEUANGAN PUSAT DAN DAERAH YANG MANTAP - Setiyono Setiyono (Jurnal Dinamika Ekonomi & Bisnis, 2005)
AbstractFrom data description of territorial original income of Territorial Income Department of Jepara Regency in the lastfive years.found  three important problems , they are 1) the awareness of community to pay tax is low, 2) the acceptance of Territorial Original Income has not been suitable with target, and 3) the professionalism  of civil servants  is less.The research metode used in this research is case study, while data are gotten by observation, interview and document study.The research result indicates that unready functions involve transaction Function ( FO), Fight over the Costumers Function (FI), Market Research and Marketing Function ( F6) and Personal Management Function ( F7). However the best alternatives to overcome the problems such as: I) Intensification of law application No. I 8, I 997 about Tax and Territory fee to use a public facility or the way in measurement and determination of tax and fee to use a public facility payet, 2) If tax and fee to the use a public facility payer experience difficulty in payment, Territory Income Department Employees to handle tax and fee to use a public facility payer through education and training suitable with need, 4) Improve quantity and quality of tax founding and elucidation so it can improve awareness of tax payer, 5) Do human approach toward tax and fee to use a public facility payer and always give illumination appreciation, 6) Buy merit of cooperate with performer instance in market research and marketing to get research result, 7) Purpose to regional government to recruit employee for Territory Income Department which is suitable  with need and need  to be development. Keyword:  Territorial  Original Income,  Situational  Objective, SWOT